Effect of Organo-Modified Nanoclay on the Thermal and Bulk Structural Properties of Poly(3-hydroxybutyrate)-Epoxidized Natural Rubber Blends: Formation of Multi-Components Biobased Nanohybrids - Salehabadi, Ali; Abu Bakar, Mohamad; Hanif Abu Bakar, Noor Hana (MDPI, 2014)
Multi-component nanohybrids comprising of organo-modified montmorillonite (MMT) and immiscible biopolymer blends of poly(3-hydroxybutyrate) (PHB) and epoxidized natural rubber (ENR-50) were prepared by solvent casting technique. The one and three dimensional morphology of PHB/ENR-50/MMT systems were studied using Polarizing Optical Microscopy (POM) and Scanning Electron Microscopy (SEM). Differential scanning calorimetry (DSC) technique was used to evaluate the thermal properties of the nanohybrids. The melting temperature (Tm) and enthalpy of melting (ΔHm) of PHB decrease with respect to the increase in ENR-50 as well as MMT content. The non-isothermal decomposition of the nanohybrids was studied using thermogravimetric (TG-DTG) analysis. FTIR-ATR spectra supported ring opening of the epoxide group via reaction with carboxyl group of PHB and amines of organic modifier. The reaction mechanism towards the formation of the nanohybrids is proposed.